Prenatal Diagnosis of Acrania in One Twin of a Dichorionic Diamniotic Pregnancy: A Case Report on Management and Perinatal Outcome - Agnieszka Żalińska; Weronika Marcinkowska; Filip Gągorowski; Łukasz Sokołowski; Michał Krekora; Przemysław Oszukowski; Agnieszka Pięta-Dolińska (Reports)
Background and Clinical Significance: Twin pregnancies are associated with an increased risk of congenital malformations. One of them is rare but lethal—acrania—which belongs to the group of neural tube defects. The pathogenesis of acrania is not fully understood. It is presumed that the underlying mechanism of its development is a disorder of migration of mesenchymal tissue. The presence of an acrania in one of the twins may lead to complications such as polyhydramnios, preterm labor, or, in severe cases, an intrauterine death in one or both twins. Case Presentation: A 30-year-old woman (G4P4) was admitted to the Labor Department of a tertiary hospital in 30+3 weeks due to preterm labor. The patient was in a dichorionic diamniotic twin pregnancy with a single lethal fetal anomaly and severe polyhydramnios of a second twin. Hence, the caesarean section was immediately performed. Both twins were admitted to the Neonatology Department. The healthy neonate was hospitalized and discharged after 42 days in good condition. Palliative care for the twin with acrania was provided. Conclusions: Early detection of acrania in twin pregnancies is critical. It allows the implementation of appropriate management and targeted counseling, thereby minimizing the risk of complications both for unaffected twins and the mothers. Our case is a good model of action where a twin pregnancy with a diagnosed lethal defect in an ambulatory setting was managed, providing holistic specialized care.